Cardiovascular Risk Stratification and Blood Pressure Variability on Ambulatory and Home Blood Pressure Measurement - Boggia, José; Asayama, Kei; Li, Yan; Hansen, Tine Willum; Mena, Luis; Schutte, Rudolph (Current hypertension reports, 2014)
Variability is a phenomenon attributed to most biological processes and is a particular feature of blood pressure (BP) that concerns many physicians regarding the clinical meaning and the impact on their clinical practice. In this review, we assessed the role of different indices of BP variability in cardiovascular risk stratification. We reviewed the indices of BP variability derived from ambulatory BP monitoring (day-to-night ratio, morning surge of BP, and short-term BP variability) and home BP measurement (standardized conventional BP measurement and self-BP measurement), and summarized our recent results with the intention to provide a clear message for clinical practice. Conclusion: BP variability, either derived from ambulatory BP measurement or home BP measurement does not substantially refine cardiovascular risk prediction over and beyond the BP level. Practitioners should be aware that BP level remains the main modifiable risk factor derived from BP measurement and contributes to improving the control of hypertension and adverse health outcomes.